The development of Islamic political Ideology until the middle of the nineteenth century - A.L. Ali Saud Shkahi (Genius Journals, 2023)
For understand the nature of the development of Islamic political Ideology, it was necessary for the researcher to trace the course of the history of that Ideology since its inception at the hands of the Holy Prophet Muhammad (may God bless him and his family and grant him peace) and the construction of a government based on Islamic teachings, passing by what happened after his death, and the emergence of many Islamic groups and sects that differed in their perceptions about the authority, the legitimacy of the government and the limits of the individual in it, until the middle of the nineteenth century AD. In this paper we divided the study to introduction Islamic political Ideology and the reasons that led to the choice of the subject and the most important sources that I referred to, and the first section dealt with Islamic doctrines and their political differences, the second section has traced the development of Sunni political Ideology ruling at the time, while highlighting in the second section the development of Shiite political Ideology after entering the era of backbiting and disagreement about the limits of the powers of the mujtahids (narrators of hadith). In conclusion, the study concluded that this development was subject to the circumstances of each stage it went through, and the differences of its groups affected the gradual development of Islamic political Ideology until the middle of the nineteenth century.
Keywords: Political thought; Sunnis; Shiites; Kharijites